Effect of autologous platelet-rich plasma treatment on patients with thin endometrium - Tung Nguyen Thanh; Ai Hoang Van; Son Trinh The; Lan Do Ngoc; Hang Doan Thi; Trang Quan Van; Khoa Ba Tran; Sang Trieu Tien (Revista Cubana de Medicina Militar)
Introduction: The success of frozen embryo transfer cycles depends on a delicate interaction between embryo quality and endometrium. Low pregnancy rates are associated with a thin endometrium. Objective: To evaluate the effect of autologous platelet-rich plasma treatment on patients with thin endometrium. Methods: In 34 patients with thin endometrium (< 7 mm), canceled in the previous frozen embryo transfer cycles, autologous platelet-rich plasma was prepared, from autologous peripheral vein blood; intrauterine infusion was given during hormone replacement therapy in frozen embryo transfer cycles. Frozen embryo transfer was performed when the endometrium thickness reached ≥ 7mm. Results: Six patients canceled the embryo transfer cycle due to endometrium thickness did not reach 7 mm; 28 patients got endometrial thickness ≥ 7 mm and performed frozen embryo transfer. The endometrial thickness was 7.5 ± 0.8 mm, which was significantly thicker than in the previous cycles (5.6 ± 0.79 mm) with p< 0.002, the implantation rate was 23.07 %, and the clinical pregnancy rate was 12/28 (42.8 %). Conclusion: Autologous platelet-rich plasma improves the endometrial thickness and the pregnancy rate outcomes in women with thin endometrium.